Evaluation of dispatching rules for flexible manufacturing system - Koh, Kok Seng. (2010)
In this project, three dispatching rules are evaluated based on system flexibility in a flexible manufacturing system (FMS). The three types of dispatching rule are earliest due date (EDD), least reduction in entropy (LRE) and least relative reduction in entropy (LRRE). The system is studied under two input rules, level production rate (LPR) and same part type (SPT), three levels of system availability (50%, 75% and 95%) and three levels of work-in-progress (WIP), 18, 27 and 36 fixtures. A static dispatching rule (EDD) is used to compare the performance with two entropy-base dispatching rules, namely LRE and LRRE. The manufacturing system would be a medium size cell which consists of 5 machines and 3 product types. The performance measures of interest are cycle time and part throughput rate.